Implementation of Financial Strategy and Business Management in Sustainable Market Development in Buahan Kaja Village - Putu Diah ASRIDA; I Ketut Johny Pramanda PUTRA (PT Keberlanjutan Strategis Indonesia, 2025)
The Community Partnership Program (PKM) implemented at Buahan Kaja Village Market has demonstrated significant results in improving the financial and managerial capacity and green economic practices of traders. Following the training, understanding of daily cash flow recording increased from 30% to 85%, and separation of personal and business finances from 25% to 75%. In terms of stock management, understanding increased from 40% to 80%, while the use of business support tools such as calculators and safes jumped from 35% to 78%. Beyond the financial aspect, the training also successfully built environmental awareness: waste sorting practices increased from 20% to 70%, and awareness of stall cleanliness and hygiene increased from 45% to 85%. These results demonstrate that the educational and practical approach of the training, coupled with the provision of simple technology, is effective in building the foundation for more orderly, efficient, and sustainable small businesses. To maintain long-term impact, continued mentoring and the integration of digitalization into daily business practices are needed to strengthen the transformation of traditional markets into healthy and environmentally friendly business ecosystems. The novelty of this program lies in its integrated approach of financial literacy, management, and green economic practices, simultaneously applied in the context of village markets, a practice that has been rare until now. Future recommendations include strengthening groups through integration with formal institutions, so that program sustainability is embedded in internal institutional capacity, rather than solely dependent on facilitators.